Corak Nalar Falsafah Kalam Abu al-Asy’ari dalam al-Luma’ - Syahuri Arsyi (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2022)
The subject of this article is the philosophical reasoning patterns in the work of Abu Hasan al-Asy'ari, titled "al-Luma' fi al-Raddi 'ala Ahli al-Zaighi wal al-Bida'". This study uses a historical factual approach based on the al-Luma' texts and contributes to the development of the discourse on kalam philosophy, particularly in Indonesia. The philosophical reasoning patterns in al-Luma, according to al-Asy'ari, consist of dominant reasoning methods such as stoic, platonic, and Aristotelian. These methods are used to counter the dogmatism of conservative Sunnis and Mu'tazilah rationalism, as well as the opinions of Mujassimah theology and Musabbihahism. The reasoning is applied using the religious-rationalism of Mu'tazilah and religious-textualism of Salafism. Abu al-Hasan al-Asy'ari's work, "al-Luma' fi al-Raddi 'alaAhli al-Zaighiwa al-Bida'" is considered one of the significant works in the field of Islamic theology that contributed to the establishment of the foundations of Islamic theology, allowing it to survive until today as the teachings of Ahl al-Sunnah wa al-Jama'ah. However, in discussing this work, al-Asy'ari mostly relies on reasoning patterns built on Stoic, Platonic, and Aristotelian logic. These patterns of reasoning are used as a counter to the dogmatism of conservative Sunnis and Mu'tazilah rationalism, as well as the Mujassimah school and the Musabbihah group by applying the Mu'tazilah-rational-religious method and the Salafiyah-religious-textualist method.  Keywords :  Philosophical reasoning, kalam, Abu Hasan al-Asy’ari, al-Luma’